Religion under bureaucracy policy and administration for Hindu temples in South India - Presler, Franklin A. (Cambridge Cambridge University Press, 1987)
Religion under Bureaucracy is an innovative study of religion and politics in the south Indian state of Tamil Nadu which focuses on the relationship between the state and the central religious institution of the area, the Hindu temple. Religion, politics, economy and culture intersect in the temple and Tamil Nadu has 52,000 in all, many richly endowed with land and prominent locally as sources of patronage and economic and political power. Dr Presley examines the institutional challenge that Hindu temples have presented to the developing South Indian state over the last century and a half and the ways in which a government publicly committed to non-intervention in religious matters has come to involve itself deeply in temple life - establishing a presence in temple management, regulating the use of the temple's material and symbolic resources and, beyond this, seeking to control many details of Hindu organisation, economy and worship.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Hindu temples -- India, South; Hinduism -- India, South -- Government; Hinduism -- India, South -- Government; Hindu temples -- India, South; Hinduism and state; Hindu temples ; India, South; Hinduism ; India, South ; Government